2018
DOI: 10.1007/s12098-018-2618-z
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hematopoiesis in Beta Thalassemia: A Case Series

Abstract: Extramedullary hematopoiesis (EMH) is a normal response to failure of hematopoiesis at its normal site i.e., bone marrow. It is a manifestation of many congenital hemolytic anemias and marrow failure secondary to myelodysplastic syndromes. Usually, extramedullary myeloid proliferation occurs in liver, spleen and lymph nodes. However, there are many unusual sites where EMH can occur. The authors report two cases of intracranial extramedullary hematopoiesis in beta thalassemia. In one of these patients, epidural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…We found ischemic foci in the cerebral white matter in 3 of our patients. In recent studies, thromboembolic events were reported with a rate of 0.9–29% in thalassemia patients [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. These ischemic foci that we saw in our patients were minimal areas due to microemboli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found ischemic foci in the cerebral white matter in 3 of our patients. In recent studies, thromboembolic events were reported with a rate of 0.9–29% in thalassemia patients [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. These ischemic foci that we saw in our patients were minimal areas due to microemboli.…”
Section: Discussionmentioning
confidence: 99%
“…Dural thickening due to extramedullary hematopoiesis is extremely rare. Studies of dural thickening resulting from intracranial extramedullary hematopoiesis in children with thalassemia are generally at the level of case reports [ 18 , 19 ]. In our study, we detected dural thickening in 1 patient.…”
Section: Discussionmentioning
confidence: 99%
“…Extramedullary hematopoiesis (EMH) is a compensatory physiological response of the organism to the failure of hematopoiesis at the bone marrow, which occurs commonly in patients with chronic hemolytic anemia or diseases with ineffective erythropoiesis [3]. Usually, extramedullary production of blood precursor cells occurs in the spleen, liver, or lymph nodes.…”
mentioning
confidence: 99%
“…However, cases with EMH in the adrenals, thymus, pleura, skin, gastrointestinal tract, and paranasal sinuses have been described [4]. Intracranial EMH is extremely rare, and only cases involving the dura mater have been described [3]. To the best of our knowledge, no cases of intracranial intraparenchymal EMH have been described.…”
mentioning
confidence: 99%
See 1 more Smart Citation